The spiritual way to desistance? - Susanne Alm; Enes Al Weswasi; Lena Roxell (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract In the years 2001-2019, the Swedish Prison and Probation Service operated religious retreat activities at the high-security prison in Kumla, to which prisoners serving long-term sentences could apply. While the activities were not specifically implemented to reduce recidivism, a process evaluation conducted in 2014-2016 showed that the participants expressed great hope that these experiences would help them desist from crime. The current study examines actual rates of desistance and recidivism among former participants in the religious activities.